An econometric study of the Phillips curve with inflationary expectations in the Saudi economy for the period 1997-2022 - Matyori, Emad Adnan (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aims to investigate the applicability of the Phillips curve with inflationary expectations to the Saudi economy for the period 1997-2022 AD. To achieve this goal, econometrics was employed using the ARDL methodology. For a model that includes the unemployment rate and inflationary expectations as independent variables on the dependent variable: the inflation rate; The study concluded that the Phillips curve with inflationary expectations does not apply to the Saudi economy for the period 1997-2022 AD. Accordingly, the study recommended: Economic theories and models need to be examined and tested before application through economic policies.
Keywords: Unemployment; inflation; Phillips curve; Phillips curve with inflationary expectations